Modified Gap Arthroplasty for Temporomandibular Joint Ankylosis Following Radiotherapy for Rhabdomyosarcoma: Report of an Unusual Case and Brief Literature Review - Zhang, Jianfei; Dai, Liyan; Abdelrehem, Ahmed; Wu, Jinyang; Li, Xiaobo; Shen, Steve Guofang (Frontiers in Oncology, 2021)
Radiotherapy at the temporomandibular joint (TMJ) area often results in trismus, however, post radiation ankylosis is extremely rare and has not been previously reported in literature. Radiation is known to impact the vasculature of bony structures leading to bone necrosis with certain risk factors including surgical intervention, even teeth extraction, that could lead to osteoradionecrosis. Accordingly, gap arthroplasty for such case seemed rather challenging. In this report, we introduce for the first time, a rare case of temporomandibular joint ankylosis post radiotherapy for management of rhabdomyosarcoma in a 12 years-old boy. A modified gap arthroplasty technique combined simultaneously with pterygo-masseteric muscle flap was applied to lower the risk of osteoradionecrosis due surgical trauma at irradiated area. Computed tomographic scan on the head indicated that the TMJ architecture was completely replaced by bone, with fusion of the condyle, sigmoid notch, and coronoid process to the zygomatic arch and glenoid fossa. The patient’s problem was totally solved with no osteoradionecrosis or relapse of ankylosis observed at follow up visits. Herein, the modified gap arthroplasty combined with pterygo-masseteric muscle flap could be recommended to be applied on other cases of ankylosis especially after receiving radiotherapy.